Física e Geociências: uma proposta interdisciplinar para o ensino de Termodinâmica e Ondulatória - Retamero, Alex Amilton Costa (2019)
The aim of the work was to verify the limit and contributions of the association between Physic and Geosciences in the High School. To this, two Potentially Meaningful Teaching Units (PMTUS) were developed based in either theories (or models): Interdisciplinary Island of Rationality (IIR) of Gerard Fourez and of the David Ausubel's Theory of significant learning. Developed in 2017 for the second year students of a private school in Curitiba, Paraná, Brazil, the PMTUS were applied from contents of Thermodynamic and Waves. These contents were approached from the study of Climate and Interior Model of the Earth. Preliminary results indicate that the association of Physics and Geosciences can motivate students and give meaning to the contents studied.